The system of faunacomponents conception and its application to qualify the degree of naturalness of fish assemblages - Sály, Péter (Acta Agraria Debreceniensis, 2007)
The increase of species richness in communities of natural biogeographic regions in an anthropogenic way can be expressed as biogeographic pollution. Where there is contaminated fauna, one must investigate how this occured. I studied how the members of Hungarian fishfauna could be present resident and have managed to workout a so-called system of fauna component conception which is suitable for this requirement.The expression of ’faunacomponent’ includes other expressions. That kind of species belong to a certain faunacomponent that reached the studied area in the same way. Species reached the studied area without an anthropogenious contribution are qualified as native fauna components. These kind of species are endemic species, occasional species and settlers. In contrast to native faunacomponents, some kind of human influence is always detectable in connection with the way reached the studied area by non-native species. Accordingly, group of non-native species includes directly or indirectly facilitated settlers, species that are introduced accidentally and those introduced intentionally. It is obvious that classifying a given species could be construed solely in connection with a certain area.Applying Shannon diversity index I have initiated the assemblage natural index (ANI) in order to show a way how to use the system of faunacomponent conception in practice. ANI refers to the degree of naturalness of faunistical samples. If ANI > 1 it means there are not any non-native species and ANI < 1 it means there are some non-native species in the sample respectively. In the latter case ANI decreases proportionally with the number of non-native species and specimens. In that special case when only one specimen of only one non-native species can be found in the faunistical sample ANI = 1.